Gut microbiota differences between healthy older adults and individuals with Parkinson's disease: A systematic review. (May 2020) - Nuzum, Nathan D.; Loughman, Amy; Szymlek-Gay, Ewa A.; Hendy, Ashlee; Teo, Wei-Peng; Macpherson, Helen
Highlights: Abundance of butyrate producing bacteria is lower in PD compared to control groups. α-diversity is seemingly not reduced in PD compared to controls. PD pathophysiology may involve decreased abundance of butyrate producing bacteria. Abstract: The 'Dual Hit' hypothesis, stating that Parkinson's disease (PD) begins via olfactory pathways and the gut, and the gastrointestinal symptoms PD individuals face, have largely driven the interest of the gut's involvement in PD. Studies have since observed gut microbiota differences between PD groups and controls, with these alterations potentially relating to PD pathophysiology. However, differences in the studies' methodologies precludes unanimity on the relationships of gut microbiota to PD. Thirteen observational case-control studies investigating gut microbiota in PD and controls were reviewed to assess how microbiota abundance and diversity relates to PD. Nine studies showed butyrate producing gut microbiota had lower abundances in PD compared to controls. Three studies reported α-diversity was higher, with one reporting it was lower, in PD compared to controls. Given most studies show abundance, not diversity, differences of butyrate producing bacteria between groups, we propose abundance differences are more associated with PD than microbiota diversity. As current research is observational, investigating how specific bacteria and their metabolites may alter throughout PD progression is warranted.